El pensamiento político liberal centroamericano del siglo XIX: José Cecilio del Valle y Antonio Batres Jáuregui - García Giráldez, Teresa (Revista Complutense de Historia de América, 2010)
The article analyzes some aspects of the debate on the nation, whose protagonists were two Central American liberals: Jose Cecilio del Valle and Antonio Batres Jauregui. Both can be considered the founding intellectuals of liberal and moderate positivist thought –the former pertaining to the early years of the XIX century and the latter to the century’s final years– each with different and contrasting views regarding the integration, in the nation, of the subordinate sectors.